Prevalence of vitamin d deficiency and hypervitaminosis d among adult patients admitted to the tertiary care hospitals in Turkey - YAVUZ, DİLEK; APAYDIN, TUĞÇE; HAKLAR, GONCAGÜL (My University, 2022)
Objective: Vitamin D deficiency is a common health problem around the world. This study aimed to evaluate the nationwide prevalence of vitamin D status in tertiary care hospitals in Turkey. Methods: Retrospectively, the data on vitamin D levels from 33 tertiary care hospitals’ clinical biochemistry laboratories around Turkey between January and December were collected. Results: In total, 706 434 serum samples from adult subjects (female/male: 469 028/237 406; 66.4%/33.6%) were included. While vitamin D levels were sufficient in 20.3% (n=14 222), they were insufficient in 21.9% (n=154 360) and deficient in 57.8% (n=408 882). We observed the highest rates of deficiency in those aged between 18 and 29 years (62.9%, n=70 235) and lowest rates between 60 and 69 years (52.3%, n=61 121) and between 70 and 79 years (52.3%, n=32 397). Hypervitaminosis D was detected in 5.5% of adult subjects; highest rates of hypervitaminosis D were observed in those who were over 80 years (6.6%) and 70-79 years (6.5%) and the lowest in 18-29 years (2.8%). Discussion: In this cohort, over half of the subjects admitted to the tertiary care hospitals in Turkey had vitamin D deficiency and required vitamin D supplementation. The elderly population had the lowest prevalence of vitamin D insufficiency and the highest prevalence of hypervitaminosis D.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); Endokrin ve Otonom Sistemler; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; 25-Hydroxyvitamin D; vitamin D; vitamin D deficiency